La utilización de la administración financiera como herramienta de dirección en las empresas cubanas. - Cruz Montero, Juan José (2018)
The Cuban economy is immersed in a group of transformations from the structural point of view, both microeconomically and macroeconomically, and this plays a fundamental role in updating the Cuban economic and social model.The following study presents the results obtained in the research carried out, in which a survey was carried out on 165 managers of the Azcuba Sugar Group, interviews were also conducted with a group of sugar sector managers belonging to Cuban national companies regarding the use of Financial management as a management tool. The result obtained with the application of these instruments led to the clarification of the current state of the problem in our sector and highlighted the need to reveal and systematize conceptual elements about the functions of financial administration that best fit the specific conditions of Cuba.It is necessary to contribute to the reflection on the role of financial management in business efficiency and its expression in Cuban companies, taking into account the current importance of investment and financing processes, oriented towards the production and marketing of New and / or improved products for the increase of exports and import substitution with the consequent purpose of the increase in the obtaining of foreign exchange and saving of material and monetary resources, as well as the role of the training of the executives in these matters.